2021
DOI: 10.31940/jasl.v5i1.2281
|View full text |Cite
|
Sign up to set email alerts
|

Figurative language used in Blackpink featuring Selena Gomez's song lyric "Ice Cream": A discourse analysis

Abstract: A pop song is one of the popular genres widespread in society. The label 'popular' is used as it covers a diverse range of masses, started from pre-dominantly youth to adult, that target them as the market. To the extent of the popular meaning, a song is supported with alluring music video clips, entertaining musical instruments, and lyrics that make an addiction by turning the repeat mode on a music player. Regardless, no all of the songs carried by singers incorporate lyric meanings of what they indeed seem.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Figurative language, as discussed by Allo (2022) and Kasma et al (2021), is prevalent in literary works including poems, short stories, and novels, allowing authors to express their thoughts creatively. This form of language transcends the literal interpretation, challenging readers to engage their imagination for a deeper understanding of the text (Gunawan et al, 2021;Ismail et al, 2020;Yanto & Siga, 2023). It employs metaphorical language to enrich communication and underscore the intended message, thereby enhancing the literary piece's appeal and significance (Indarti et al, 2023;Taufik & Cahyati, 2022;Santika & Syafryadin, 2023;Karimah et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Figurative language, as discussed by Allo (2022) and Kasma et al (2021), is prevalent in literary works including poems, short stories, and novels, allowing authors to express their thoughts creatively. This form of language transcends the literal interpretation, challenging readers to engage their imagination for a deeper understanding of the text (Gunawan et al, 2021;Ismail et al, 2020;Yanto & Siga, 2023). It employs metaphorical language to enrich communication and underscore the intended message, thereby enhancing the literary piece's appeal and significance (Indarti et al, 2023;Taufik & Cahyati, 2022;Santika & Syafryadin, 2023;Karimah et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Using figurative language serves a multifaceted purpose in music, academia, and scientific knowledge [3]. Far from being uncommon or purely poetic, figurative language is an ever-present element in spoken and written communication.…”
Section: Introductionmentioning
confidence: 99%
“…The researcher also explained that using figurative language in the novel makes the reader can imagine the story. (Gunawan et al, 2021) whereadvertisements or commercials are also analyzed with figurative language. The study from (Sofyan et al, 2020) under the title Using Figurative Language in Cosmetic Advertisements on Indonesian Television, Wibowo (2016) which found that there were eleven sentences categorized into eight types of figurative language such as personification, paradox, metaphor, apostrophe, symbol, allegory, hyperbole, and repetition.Next, the other study from Pramono (2020) which showed that all types of impoliteness strategies (bald on record, positive impoliteness, negative impoliteness, sarcasm or mock impoliteness, and withhold politeness) were done by Gordon Ramsay to female participants and four types of impoliteness strategies (bald on record impoliteness, positive impoliteness, negative impoliteness, and sarcasm or mock impoliteness) performed on male participants.Figurative language on reality TV-show was difficult to find.…”
Section: Introductionmentioning
confidence: 99%